Understanding the perceived reasons and practices related to gender preferences in an urban population of Puducherry: an exploratory study - Naik, Bijaya Nanda; Majumdar, Anindo; Sahu, Swaroop Kumar (International Journal of Contemporary Pediatrics, 2017)
Background: Declining child sex ratio in India even after enactment of PCPNDT Act is a major concern from public health point of view. Objectives: 1) To find out the perceived reasons and preference for the gender of the prospective child 2) to find out practices related to ultrasound (USG) scanning during pregnancy and abortion and 3) to find out the child sex ratio in the selected urban field practice areas of JIPMER, Pondicherry. Methods: A community-based explorative study was conducted during the months of June and July 2013. A pre-tested semi-structured questionnaire was used to collect information on the socio-demographic details, sex preference for the prospective child, and practices related to USG scanning during pregnancy and abortion among 270 households in the study area of urban Puducherry. One Focus Group Discussion (FGD) was organized to explore and understand the qualitative aspect of gender preference in the study area. Results: Among the respondents who had not completed their families (67), majority (60%, 40/67) didn’t have any gender preference. Out of the rest 27, 16 respondents (60%) preferred their prospective child to be male. The common reasons for male preference were 1st child being female, dowry and other financial reasons. Majority (62%) of the USG during pregnancy were done in private set up. Nearly three fourth of the abortions took place either in private set up or at home. Nearly 37 % of respondents felt that proportion of females was less in their area as compared to males. Nearly 6% (16/270) of the respondents were aware of existence of practice of sex determination and female foeticide in their area. The child sex ratio was found to be 1012 per 1000 males. Conclusions: Male preference in the backdrop of higher proportion of practice of abortion in the private set up, along with participants’ awareness of existence of sex determination practices points towards plausible female foeticide. There is a need to generate stronger evidence to confirm these suspected links.